2009
DOI: 10.3382/ps.2009-00181
|View full text |Cite
|
Sign up to set email alerts
|

Pale, soft, exudative turkey—The role of ryanodine receptor variation in meat quality

Abstract: The poultry industry has made significant advances in growth rate, feed efficiency, and breast muscle yield through intensive breeding of turkeys. However, a meat quality problem known as pale, soft, exudative (PSE) meat presents the industry with a major challenge during periods of stress, such as the onset of a prolonged heat wave. The biochemical characteristics of PSE turkey are strikingly similar to those of PSE pork. Abnormally rapid postmortem metabolism, stimulated in part by high concentrations of cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…When compared to other species, the sequence amplified by us is located at the end of hotspot 2 in the turkey a-RyR gene, which is located in a conserved region. Region 1 (1-1000 amino acids), region 2 (2000-3000) and region 3 (4000-5000) are conserved between species (Brini, 2004;Chiang et al, 2007;Strasburg and Chiang, 2009). Many diseases in humans have been linked to mutations located in regions 1 and 2 of the RyR1 gene (Brini, 2004), and according to Chiang et al (2004), more than 20 mutations that cause amino acid changes or that delete amino acids are located in these regions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When compared to other species, the sequence amplified by us is located at the end of hotspot 2 in the turkey a-RyR gene, which is located in a conserved region. Region 1 (1-1000 amino acids), region 2 (2000-3000) and region 3 (4000-5000) are conserved between species (Brini, 2004;Chiang et al, 2007;Strasburg and Chiang, 2009). Many diseases in humans have been linked to mutations located in regions 1 and 2 of the RyR1 gene (Brini, 2004), and according to Chiang et al (2004), more than 20 mutations that cause amino acid changes or that delete amino acids are located in these regions.…”
Section: Resultsmentioning
confidence: 99%
“…Four stretches of G. gallus sequence (NW_001476149, NW_001476304, NW_001479482, and NW_001484776) were identified as similar to the turkey α-RyR sequence. The NW_001476149 contig was located in the interval between nucleotides 6506 to 7405 in the turkey α-RyR transcript, which is within the region described as belonging to hotspot 2 (Strasburg and Chiang, 2009). Thus, the sequence of NW_001476149 was used to design forward (5'-AGGAAGCCGACCTCCAAC-3') and reverse (5'-TGGGGGTCATCAGCCTTC-3') primers using the Primer3Plus program (Untergasser et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In turkeys, Chiang et al (2004) reported that changes in the hotspot 1 region of the αRYR mRNA were related to the occurrence of PSE meat. This region corresponds to the N-terminal portion of the protein and some reports indicate that it is an important regulatory domain for controlling the sensitivity of the channel protein and the release of Ca 2+ (Brini, 2004;Strasburg and Chiang, 2009) (Figure 2). In broilers, this hotspot region was first sequenced and identified in our lab .…”
Section: Introductionmentioning
confidence: 99%